Perbedaan jumlah C. albicans pada permukaan poles terhadap non-poles basis gigi tiruan yang didisinfeksi dengan UVC (Laporan Penelitian): Kajian pada Resin Akrilik Heat Cured - Michelle Chyndi Vendela; Yayuk Yuliarsi (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background : The most commonly material for denture bases is heat cured acrylic resin. Dentures with a surface roughness value of more than 0.2 µm can increase bacterial colonies, fungi and plaque accumulation. Dentures can be cleaned with several techniques, one of which is with a UV device which is a new technology to kill pathogens and microorganisms. UVC (254 nm) is capable of breaking molecular bonds and disrupting DNA or RNA which causes the death of various microorganisms. Method : This research method is a laboratory experimental with a post test group design. The sample used heat cured acrylic resin with a size of 20 mm x 10 mm x 3 mm. Disinfection was carried out using UVC for 15 minutes. Results : The results of the sample showed that there was a significant difference in the amount of C. albicans on the polished and non-polished surfaces of heat cured acrylic resin denture bases disinfected with UVC. Conclusion : After disinfection using UVC, there were significant differences in the amount of C. albicans on the polished and non-polished surfaces of heat cured acrylic resin.